Fish Bone in the Glottis of a Seventeen-Month-Old Child: A Case Report - Baidya, Smriti; Gyawali, Bigyan R (Journal of Institute of Medicine Nepal, 2021)
Foreign body aspiration is one of the leading causes of accidental death in children. Young children tend to put objects in their mouths which may additionally explain the incidence of foreign body aspiration. Laryngeal impaction of a foreign body is very rare as most aspirated foreign bodies pass through the laryngeal inlet and get lodged lower down in the airway. Inhaled foreign bodies are suspected from the history of incidence witnessed by the parent or caregiver or at times from clinical symptoms of respiratory complains not responding to medical therapy. Removal of the foreign body from the airway is the modality of treatment done via rigid bronchoscopy under general anesthesia in our setting. A rare case of foreign body aspiration with glottic impaction in very young child of seventeen months has been described here.